Biosurfaktan - Reningtyas, Renung; Mahreni, M (Eksergi, 2015)
Surfactant is an amphipilic chemical structure which contains the hydrophobic and hydrophilic groups. Surfactant has ability to lower surface tension between two liquids. Surfactant has been used in many industries, such as cosmetics, food, textile, petroleum, and pharmacy industry. Nowdays, most of surfactant used in industries are still based on petroleum resources. The applicationsof this nonbiodegradable surfactant in industry promote environmental problem. Biosurfactant is a biodegradable surfactant that produced from microorganism or natural resources. Biosurfactant produced from microorganism contains Rhamnolipid and Lipopeptide. Surfactin and Dactomicin made from microorganism with antibacterial activity are the examples. Bottle necks of the production of biosurfactant form microorganism are their slow process, high purification cost, and high product price. Biosurfactant from natural resources are potentially produced in large scale due to their fast process and relatively cheap raw material. Metil Ester Sulphonate (MES) is one of biosurfactant produced from natural resources (from palm oil). The other example is biosurfactant from esterification of carbohydrate and carboxylic acid. This paper reviews the literatures dealing with biodegradable surfactant development which can be used as a reference of a research path way and an industrial scale production of biodegradable surfactant.